Dielectric properties of BaTiO3 ceramics prepared from powders with bimodal distribution - Deshpande, S. B.; Potdar, H. S.; Patil, M. M.; Deshpande, V. V.; Khollam, Y. B. (Journal of Industrial and Engineering Chemistry, 2006)
BaTiO3 (BT) powders having bimodal distribution were synthesized successfully through a simple classical solid-state reaction route using cheap BaCO3 and TiO2 as starting materials. These powders were further processed in the form of green pellets to obtain dense BT ceramics having densities of similar to 94 similar to 96 % after sintering in air at 1350 and 1400 degrees C/4 h in air. The room temperature dielectric constant (epsilon(RT)) of similar to 1500 at 1 KHz frequency was increased to : 10000 at a Curie temperature (T-C) similar to 126 degrees C, showing a very sharp transition from a polar tetragonal to a non-polar cubic structure. The dielectric loss factor (tan 6) was similar to 1.5 %. SEM studies revealed the presence of dense microstructures having a distribution of smaller grains (size: 2 similar to 3 gm) surrounded by larger grains (>= 35 mu m). The ferroelectric hysteresis loop measurements on these samples gave values of spontaneous polarization (P-s) of similar to 12.0 mu C/cm(2), a coercive field (E-C) of similar to 2 similar to 2.5 kV/cm, and a dielectric strength (E-b) of similar to 48.0 kV/cm. DC-resistivity as high as 1.5 x 10(9) Omega-cm was obtained in these samples. All these results are quite comparable with reported ferroelectric/dielectric data and are discussed elaborately in this paper.
Keywords: BaTiO3; dielectric-ferroelectric properties; Microstructure; Sintering; stoichiometry